2021
DOI: 10.1007/s00701-021-04708-3
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality navigation in spine surgery: a systematic review

Abstract: Background Conventional spinal navigation solutions have been criticized for having a negative impact on time in the operating room and workflow. AR navigation could potentially alleviate some of these concerns while retaining the benefits of navigated spine surgery. The objective of this study is to summarize the current evidence for using augmented reality (AR) navigation in spine surgery. Methods We performed a systematic review to explore the current e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 47 publications
2
46
0
2
Order By: Relevance
“…AR systems have demonstrated a high accuracy compared to free-hand and conventional navigation in spine surgery in several clinical studies [ 38 ]. Good 3D depth perception, resulting in smooth hand–eye coordination, was provided using advanced AR visualization in combination with additional views on screens near the surgical field [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…AR systems have demonstrated a high accuracy compared to free-hand and conventional navigation in spine surgery in several clinical studies [ 38 ]. Good 3D depth perception, resulting in smooth hand–eye coordination, was provided using advanced AR visualization in combination with additional views on screens near the surgical field [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the applications of AR with the highest potential is spinal surgery. 3,4 AR has been shown previously, both in cadaver studies and in real patients, to be of clinical utility for guiding the placement of spinal hardware. [4][5][6][7][8] These studies have suggested that pedicle screw placement and tumor resection guided by AR have the potential to be highly accurate and precise.…”
mentioning
confidence: 92%
“…AR thus may be a meaningful surgical adjunct to conventional freehand pedicle screw placement or other spinal procedures and may enable comparable accuracy to robotic pedicle screw placement. 3 It may also reduce fluoroscopy-or CT-associated radiation exposure to patients and surgeons.As the applications for AR guidance in spinal surgery increase, more data are required to quantify the utility of this technology. Until this point, little has been written regarding the use of AR guidance for the placement of percutaneous thoracic or lumbar pedicle screws, particularly regarding AR head-mounted display (ARHMD) stereotac-ABBREVIATIONS AR = augmented reality; ARHMD = AR head-mounted display.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As personal computers and augmented reality (AR) equipment performance improve, it is becoming easier to handle 3D images at home. In the medical field as well, various AR devices have been used recently [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%